Poverty Reduction through Sustainable Fisheries : Emerging Policy and Governance Issues in Southeast Asia - Garcia, Arnulfo G. (Arnulfo Gonzales), 1948-; Briones, Roehlano M. (Roehlano Mariano), 1971- (Book collections on Project MUSE., 2008)
Beyond previous more simplistic approaches, this book takes a giant step towards understanding and translating into people-centered policies the actual position and complexity of fish production in Southeast Asian economies. Tackling how fi sheries and aquaculture are embedded in local and household economies and linked through dynamic supply chains to more distant, even global markets, the book makes essential policy and analytical recommendations. SEARCA and ISEAS have made a major contrib ... Beyond previous more simplistic approaches, this book takes a giant step towards understanding and tr.